Dienogest-based hormonal contraception induced changes in the ultrasound presentation of the uterus and menstrual pain - Anjeza Xholli; Anna Biasioli; Giovanni Grandi; Angelo Cagnacci (IMR Press, 2021)
Background: In young women, combined hormonal contraceptives can ameliorate menstrual pain and reduce menstrual loss, but their efficacy in adenomyosis has not been proven. The aim of this study was to investigate whether ultrasound features of adenomyosis are modified by a combined hormonal contraceptive containing dienogest. Methods: Fifty-eight out of 173 premenopausal women consecutively attending our university hospital outpatient service for contraception were enrolled in this observational study. Women with menstrual pain or heavy menstrual bleeding underwent ultrasonography. An expert sonographer diagnosed or excluded adenomyosis and fibroids via morphological uterus sonographic assessment (MUSA). The intensity of menstrual pain was quantified by each patient on a visual analogue scale (VAS). A total of 38 women with and 20 without ultrasound features of adenomyosis received dienogest-based hormonal contraceptive and had a follow-up ultrasound after 6 months of treatment. Results: During treatment, uterine volume decreased by -13.1 ± 22.1% (p = 0.001) in women with adenomyosis features, while it tended to increase in controls. Hypoechoic striation of myometrium present in 95% of cases and myometrial cysts in 5% of cases, respectively, at baseline, had completely disappeared by 6 months. Asymmetry of uterine walls decreased, with the anterior/posterior wall ratio declining from 2.8 ± 0.8. to 1.9 ± 0.7 (p = 0.0001). Heterogeneous myometrial texture, globous uterine morphology, and junctional zone alteration remained unchanged. In women with baseline adenomyosis, VAS score for menstrual pain decreased by -4.0 ± 3.6 (p = 0.0001). During treatment, a VAS score for menstrual pain close to 0 was found in all women without adenomyosis. Days of menstrual flow decreased in women with (p = 0.0001) and without (p = 0.003) adenomyosis. Conclusions: Dienogest-based hormonal contraceptives improve the sonographic features of adenomyosis and improve symptoms. Prospective data are needed to confirm these findings.